NOW that's what I call music!. Christmas classics [compact disc]. - Crosby, Bing, 1903-1977; Cole, Nat King, 1919-1965; Martin, Dean, 1917-1995; Ives, Burl, 1909-1995; Mathis, Johnny; Williams, Andy, 1927-2012; Como, Perry, 1912-2001; Autry, Gene, 1907-1998; Bennett, Tony, 1926-; Presley, Elvis, 1935-1977; Garland, Judy; Fitzgerald, Ella; et al. (UMG Recordings, Inc., 2021)
NOW Christmas Classics features twenty of your favorite holiday hits from Bing Crosby, Nat King Cole, Dean Martin, The Temptations, and more! This compilation inc ludes: White Christmas; Santa Baby; Sleigh Ride; Silent Night; Have Yourself A Merry Little Christmas; and fifteen other heartwarming holiday classics.